Uses of augmented reality in surgical consent and patient education - A systematic review. - Thomas Evans; Adam Turna; Thomas D Stringfellow; Gareth G Jones (PLOS Digital Health)
Augmented reality (AR) allows the real environment to be altered with superimposed graphics using a head-mounted-display (HMD), smartphone or tablet. AR in surgery is being explored as a potential disruptive technology and could be used to improve patient understanding of treatment and as an adjunct for surgery. The aim was to explore this use of AR and assess potential benefits for consent and patient education. A systematic review was conducted using PRISMA-SCR guidelines. 4 major bibliographic databases were searched using the terms: '(augmented reality OR mixed reality) AND surgery AND (consent OR patient education)'. Included papers evaluated an AR intervention on consenting patients for enhancing surgical consent or education about a procedure. Non-English language papers and studies which did evaluate an intervention were excluded. Three reviewers screened all abstracts and full text papers for inclusion. The review protocol was prospectively registered with PROSPERO (ID: CRD42020207360). 52 records were identified. Following removal of 13 duplicates, 21 were removed after abstract screening leaving 17 articles for full assessment. One article was a letter and 8 did not evaluate interventions, leaving 8 articles published between 2019 and 2023. 3 papers were randomised controlled trials comparing AR enhanced processes to standard consent, 2 cohort studies evaluated patient satisfaction with AR interventions and there was one randomised crossover trial of AR against traditional consent consultation. The Cochrane risk of bias tool was used most studies were deemed as high risk of bias. Patient satisfaction and understanding were improved using AR. However, advantages over other enhanced techniques are less clear. Using AR to enhance written literature was shown to require less mental effort from patients and was preferred to standard resources to understand complex surgery. The few randomised trials are limited by bias and lack of power calculation, highlighting the need for further research.